Preventing and countering of corruption in modern Ukraine: on the example of foreign countries experience - Barehamian, Siuzanna; Dudar, Natalia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article examines the experience of foreign countries in preventing and counteracting corruption in order to develop directions for improving the legal mechanism of Ukraine. It is concluded that countries such as South Korea, the United States of America, the Republic of Singapore actively and successfully fight corruption through effective programs. Implementation of such anti-corruption measures in Ukraine should have a good effect on the «anticorruption indicator» in the state.